PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN KEMAMPUAN MEMBACA BAHASA INGGRIS PADA ANAK TUNAGRAHITA RINGAN DI SLB - Dewi Puspo R; Starry Kireida K (Fakultas Psikologi Universitas Wijaya Putra, 2020)
Mental retardation is someone who experiences mental retardation which includes gradations ofmild, moderate, and severe which causes the disruption of the process of capturing, obtaining, andunderstanding information. Suffering of mentally retarded children stems from the limitations ofintelligence which makes it difficult for him to attend education programs in ordinary schoolsclassically. Besides that they experience retardation in adjusting to the environment, they are alsoless capable in thinking things that are abstract, difficult, and convoluted. The purpose of thisstudy is to improve the ability to read English in mild retarded children by applying the make amatch type of cooperative learning model. This research uses a qualitative approach. Datacollection is taken from the results of observations. This study uses classroom action researchprocedures. Data analysis techniques used are reduction, data display, and drawing conclusions.The results showed that the application of the make a match type of cooperative learning modelcould improve English reading skills in mild retarded children in SLB